Study on the Fabrication of Nano-SiC/Ni-P Composite Coatings with the Assistance of Electromagnetic-Ultrasonic Compound Field - Zhou, H.Z.; Wang, W.H.; Gu, Y.Q.; Fang, X.X.; Bai, Y.Q. (Проблемы прочности, 2017)
Electroless nanocomposite platings were fabricated while the magnetic field strength and ultrasonic parameters were controlled. The effect of the complex field on the composite platings’ deposition process was discussed. The results show that composite coatings fabricated by a complex magnetic field had better density and homogeneity than coatings processed without the influence of external fields. The time-step deposition discussions indicate that the extra magnetic field accelerates the motion of the composite particulates in the bath through the action of the Lorentz force and promotes the nucleation and growth process of composite particulate clusters. The mechanical energy generated by the ultrasonic vibration activates the substrate surface and promotes the deposition of the Ni2+ in the plating solution on the substrate surface. While the complex field is functioning, ultrasonic and magnetic interactions play an important role in the fabrication of the uniform and dense nano-SiC/Ni-P composite coatings, which consist of amorphous spherical Ni-P/SiC particle clusters with 200 nm diameter. The nanoindentation hardness of these composite coatings was approximately 0.15 GPa.